Adapting futures scenarios to study UK household energy demand. Issue 5 (5th December 2019) - Banchs-Piqué, Miquel; Hutchinson, David J; Becerra, Victor M; Gaterell, Mark
Abstract : Greenhouse gas emissions originating from the built environment play a significant role towards climate change. Carefully planning the future of the building sector is key to mitigating these emissions. Addressing this problem by using a predictive approach may miss possible futures that cannot be anticipated. Using explorative scenarios to perform futures analysis helps widen the range of futures taken into account, which minimises this risk. Tools that use scenarios to help study the resilience of sustainable solutions for the UK urban environment are already available. However, they do not facilitate in-depth analysis of future household energy demand. This paper considers how one such tool, 'Designing Resilient Cities' (DRC), could be modified appropriately. It includes ( a ) a series of indicators representing factors affecting the energy demand in dwellings and ( b ) their characteristics for each scenario to complement the narratives in DRC. As a case study to validate these additions, the resilience of a recommendation to decrease domestic electricity consumption is evaluated.